Patterns and predictors of repeated violent suicide attempts: a retrospective clinical study from an acute trauma care setting - Szeifert, Noemi Monika; Balint, Lajos; Gonda, Xenia (Frontiers in Psychiatry, 2026)
BackgroundViolent suicide attempts pose a major challenge to trauma and psychiatric services due to their high lethality and complex clinical profiles. While non-violent suicidal behaviors have been extensively studied, considerably less is known about the recurrence of violent suicide attempts. This study examined demographic and clinical factors associated with repeated violent suicide attempts in Hungary.MethodsA retrospective chart review was conducted at the Dr. Manninger Jenő National Trauma Center in Budapest among patients admitted between January 2015 and December 2024 following a violent suicide attempt. Electronic health records provided sociodemographic, psychiatric, motivational, and method-related data. Subgroup and logistic regression analyses were used to identify predictors of repetition.ResultsThe final sample comprised 327 individuals (222 males, 105 females; mean age = 46.95 years, SD = 19.5). Repeated violent suicide attempts were observed in 18% of females and 10% of males. Overall, 31% of violent suicide attempters had a history of a prior non-violent suicide attempt followed by a transition to violent methods. Males had approximately threefold higher odds of transitioning from non-violent to violent methods. Among suicide deaths, 76% occurred in males, and 96% were fatal at the first attempt. Personality disorders (OR = 4.15, p = 0.028), substance use disorders (OR = 2.86, p = 0.005), and sedative/hypnotic medication dependence (OR = 3.72, p = 0.009) were significantly associated with repeated violent suicide attempts, particularly among males. Polytoxicomania was associated with nearly fourfold higher odds of repetition (OR = 3.97, p = 0.0004). A history of a prior violent suicide attempt was the strongest predictor of repetition (OR ≈ 660, p < 0.000001), independent of age and sex. Acute psychotic symptoms, while not inherently motivational in themselves, emerged as the most frequently reported proxy associated with violent suicide among repeat attempters, followed by relational conflict, existential crisis, and chronic illness.ConclusionRepeated violent suicide attempts constitute a distinct and exceptionally high-risk clinical phenotype. Prior violent attempts, male sex in the context of repetition, personality disorders and substance abuse—particularly polytoxicomania—emerged as salient risk markers. These behaviors appear to arise at the intersection of prior violent conduct and acute substance-induced psychopathological states, notably psychotic symptoms with impaired reality testing and heightened impulsivity. Early identification and integrated psychiatric care, initiated during acute trauma management and maintained throughout rehabilitation, are critical to mitigating subsequent suicide risk in this vulnerable population.